A Review On Water Quality Monitoring Methods Based On Electronics And Optical Sensing - Nur Afiqah Razman; Nur Ain Insyirah Muhammad Kamil; Siti Nadhirah Zainurin; Wan Zakiah Wan Ismail; Irneza Ismail; Juliza Jamaludin; Mus’ab Sahrim; Khairul Nabilah Zainul Ariffin; Sharma Rao Balakrishnan (Semarak Ilmu Publishing, 2024)
Indexed by SCOPUS/MYCITE